Using an implementation research approach to assess the birth outcomes associated with the 2016 World Health Organization antenatal care policy across states in Nigeria: multilevel analysis of national survey data - Christiana Ikemeh; Adedayo O. Adeyemi; Leah M. Frerichs; Christopher M. Shea; Justin G. Trogdon (BMC Global and Public Health)
Abstract Background In 2017, the Nigerian Federal Ministry of Health adopted and implemented the 2016 World Health Organization (WHO) antenatal care (ANC) policy, including the eight-visit ANC (8vANC) recommendation, to improve ANC uptake and reduce perinatal deaths. This study aimed to examine the impact of the 2016 WHO ANC policy implementation on selected birth outcomes in Nigeria. Methods This research applied an implementation research approach to assess cesarean births, low birth weight (LBW), and perinatal death outcomes associated with the 2016 WHO ANC policy implementation across states in Nigeria. We used multilevel mixed-effects logistic regression model to perform secondary analyses on a matched sample of mothers and children, n = 10,864. A main fixed effect variable was generated from maternal adherence as penetration-fidelity and categorized as “ < 8vANC and partial/non-concordant,” “ < 8vANC and concordant,” “8vANC and partial/non-concordant,” and “8vANC and concordant.” We measured “concordant” as maternal self-reported adherence to five selected ANC components (timing of first ANC visit, blood pressure measurement, tetanus vaccinations, urinalysis, and blood sample test), whereas partial/non-concordant was defined as the receipt of fewer components. Results There was no significant association between penetration-fidelity and cesarean births. Compared with children born to mothers who were categorized as “ < 8vANC and partial/non-concordant,” the final adjusted models indicated that penetration-fidelity was significantly associated with reduced odds of LBW among children of mothers who were categorized as “8vANC and concordant” (OR: 0.38, 95% CI: 0.20–0.71, p = 0.003) but with increased odds of perinatal death among children birthed to mothers categorized as “8vANC and concordant” (OR: 1.85, 95% CI: 1.05–3.26, p = 0.032). There was no statistically significant between-state residual variation associated with birth outcomes. Overall, multiparity was associated with increased odds of LBW and perinatal death, whereas advanced maternal age was associated with reduced odds. Conclusions Our findings suggest the need for more nuanced ANC promotion campaigns that would target the varied maternal age and parous spectrum along the maternal and child health continuum. Further research is needed to evaluate the degree to which the state-level implementation of the policy may have also influenced adherence to the 2016 WHO ANC recommendations.